Koreografi Tari Dulang Badarak di Sanggar Tari Galatiak Kota Solok - Andini, Shavira Putri; Nerosti, Nerosti (Lembaga Yasin AlSys, 2025)
This study aims to describe the choreography of Tari Dulang Badarak, as developed at Sanggar Tari Galatiak. The research is grounded in the importance of choreographic documentation as part of preserving traditional performing arts that embody cultural values and local aesthetic expression. A qualitative approach with a descriptive method was employed. Data were collected through literature review, observation, interviews, and documentation, using tools such as writing instruments, a camera, audio cassette, and flash drive. The findings show that the choreographic creation process includes the stages of ideation, exploration, improvisation, and composition. The dance is inspired by the makan bajamba tradition and children's games, developed into three main sequences: playing with dulang, communal dining, and playful drumming on the dulang. Floor patterns include A-shape, horizontal, square, and diagonal formations. The choreography comprises 19 movement variations, categorized into meaningful gestures (e.g., carrying the dulang on the head) and pure movements (e.g., swinging in zigzag patterns), which contribute to the dance’s expressive aesthetic and cultural significance. The performance is accompanied by techno music as an innovative element, while makeup and traditional Minangkabau costumes are modified to support movement comfort. The integration of these elements results in a harmonious, communicative, and visually meaningful dance performance.